With, by and for young people: Strengths-based rural youth program development in Papua New Guinea - Pamphilon, Barbara (University of Canberra, 2023)
Across the world there is a growing recognition of the important place of youth in farming systems. Therefore, it is crucial to help young people see the many futures in agri-food systems and engage them in their formative years. This presentation will focus on the potential of the youth of Papua New Guinea (PNG), a low–middle income country to the north of Australia. As with many low-income countries, PNG is experiencing a youth bulge and high unemployment as many young people drift to the city where they typically do not find work. However, smallholder farmers are a key part of national food and nutritional security as they produce 85% of the country’s food crops, hence there are many opportunities for PNG’s young people in the agri-food system. Much of the current PNG research on youth focuses on the dangers of young people’s risky behaviors to themselves and others, and on their many needs. This deficit-based approach sees young people in a risk or problem frame rather than for their strengths and as potential partners in development efforts. The presentation will show how a strengths-based program-development approach can turn the analysis from a deficit focus to understanding how an analysis of the sociocultural contexts of young people can identify what strengths can be built on, as well as identifying the diverse groups of young people. It will illustrate how a place-based analysis can utilize individual, household, cultural, and organizational assets in the design of youth development programs.